Alimentary protein deficiency aggravates mitochondrial dysfunction in animals with acetaminophen-induced kidney injury - Voloshchuk, Oksana; Kopylchuk, Halyna (Current Issues in Pharmacy and Medical Sciences, 2025)
We investigated the indicators of kidney function, the degree of ROS-mediated damage to lipids and proteins of mitochondria, the activity of antioxidant enzymes and the I and II complexes of the respiratory chain enzymes in animals with APAP-induced kidney damage and alimentary protein deficiency. Accordingly, in rats with APAP kidney toxic injury against protein deficiency, one of the mechanisms of impaired kidney function is the activation of oxidative damage to mitochondrial biomolecules. This is followed by a dysfunction of mitochondrial complexes I (NADH dehydrogenase: ubiquinone oxidoreductase) and II (succinate: ubiquinone oxidoreductase), and leads to histopathological changes in the kidney structure. Our work demonstrated that protein deficiency in the diet is a critical factor in determining the degree of structural and functional changes in the kidneys in animals with APAP kidney injury. The obtained results substantiate the rationale for assessing the organism’s supply of protein when developing a plan for nephrotoxicity management in patients with an acute acetaminophen overdose.